Longitudinal Study on the Impact of Diet on Blood Health: a 5-Year Prospective Cohort Analysis - Wadaa, Hussein Abulzahra (American Journal of Biomedicine and Pharmacy, 2025)
Background: The role of dietary patterns in maintaining optimal blood health remains incompletely understood, particularly regarding long-term effects on hematological, metabolic, and inflammatory parameters. Objective: To evaluate the 5-year impact of Mediterranean, Western, and vegetarian dietary patterns on complete blood count, lipid profile, and inflammatory biomarkers in healthy adults. Methods: We conducted a prospective cohort study with 500 participants (18-65 years) stratified by baseline dietary patterns. Annual assessments included standardized blood tests and validated food frequency questionnaires. Statistical analyses employed linear mixed-effects models with adjustment for potential confounders. Results: The Mediterranean diet group demonstrated significant reductions in LDL compared to Western diet consumers. Vegetarian participants showed lower hemoglobin levels (-0.8 g/dL, 95% CI -1.2 to -0.4, p=0.002) but markedly reduced CRP concentrations (-1.8 mg/L, 95% CI -2.3 to -1.3, p<0.001). Conclusion: Sustained adherence to Mediterranean dietary patterns confers significant hematological and metabolic benefits, while vegetarian diets require micronutrient monitoring to prevent subclinical anemia despite their anti-inflammatory advantages.